A Cylindrical Tuber Encapsulant Geometry for Enhancing Optical Performance of Chip-on-Board Packaging Light-Emitting Diodes - Xingjian Yu; Bin Xie; Bofeng Shang; Qi Chen; Xiaobing Luo (IEEE Photonics Journal)
Low light efficiency and poor angular color uniformity (ACU) are the key challenges of chip-on-board packaging light-emitting diodes (LEDs). In this paper, we demonstrate a phosphor geometry, and its controlling method for enhancing the optical performance of chip-on-board packaging LEDs, its fabrication flexibility, and availability are validated by experiments, and its effect on the optical performance is analyzed by optical simulations and experiments. The simulation results show that compared with the conventional flat geometry, the cylindrical tuber geometry can effectively improve the light efficiency and ACU, and the light efficiency enhancement increases with correlated color temperature. Experimental results show that for the case that the encapsulation layer only consists of silicone, the proposed geometry enhances the light efficiency up to 63.1%. In addition, for another case, in which the encapsulation layer consists of silicone and phosphor particles, when the average correlated color temperature (CCT) is about 5000 K, the proposed geometry increases the light efficiency by 11.7%, and the angular CCT deviations for the flat geometry and the proposed geometry are 1805 and 475 K, respectively.